2021
DOI: 10.37394/23207.2021.18.132
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Methods for Generation Z for Physical Activities: a Stable Labor Market Provision under the COVID-19 Pandemic

Abstract: Over a year has passed since the beginning of Covid-19 pandemic and the introduction of measures to limit the spread of the pandemic in Latvia. These have resulted in changes in all spheres of young people's lives, including the way they study and exercise. This study examines the role of Generation Z physical activity as a means of maintaining the well-being of the emerging workforce and the choice of teaching methods by different age groups and genders as well as the finances spent on it. The research method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Accordingly, Demir and Sönmez (2021: 684) note that the game element is an important constituent of English language instruction among Generation Z students. Similarly, Kravalis et al (2021) argue that individuals born between the late 1990s and 2010, the so-called 'digital natives' or Generation Zs, are particularly receptive to new learning tools and environments and prefer visual materials, especially videos and other multimedia, to traditional work with texts. It has also been argued that the factor of 'edutainment', or the combination of education and entertainment, is in demand among Generation Z representatives, who currently constitute most undergraduate students (Kravalis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Demir and Sönmez (2021: 684) note that the game element is an important constituent of English language instruction among Generation Z students. Similarly, Kravalis et al (2021) argue that individuals born between the late 1990s and 2010, the so-called 'digital natives' or Generation Zs, are particularly receptive to new learning tools and environments and prefer visual materials, especially videos and other multimedia, to traditional work with texts. It has also been argued that the factor of 'edutainment', or the combination of education and entertainment, is in demand among Generation Z representatives, who currently constitute most undergraduate students (Kravalis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Arrosagaray, González-Peiteado, Pino-Juste and Rodríguez López (2019: 31) state that online and hybrid (or 'blended') courses 'offer flexible learning formats for learners of all ages in the way of tailor-made instruction which can adapt to their needs and expectations'. However, certain teaching methods lend themselves better to the traditional face-to-face (F2F) classroom: whereas lectures can be effectively delivered online and in person, group projects, round tables and discussions are formats that are harder to replicate in the online environment (Kravalis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Since early 2020, the COVID-19 pandemic has spread fast globally and severely impacted people's health [1]. One concern during the pandemic has been the level of inactivity among people, especially Gen Z. Gen Z, the "net" generation or the digital natives, is currently studying in secondary and higher education or has recently entered the employment market [2]. Segmenting the market by differentiating generational groups is a common way to understand consumer behavior better.…”
Section: Introductionmentioning
confidence: 99%
“…Covid-19 has affected all areas of human activity, including physical activity and exercise. Various studies have reported reduction in sport participation and physical exercise among different age groups, a tendency occasionally associated with the increase in occurrence of depressive moods, deterioration of emotional well-being, as well as some indulgence in unhealthy habits, such as overeating, augmented use of alcohol and smoking (Kravalis et al, 2021b;Baranauskas et al, 2022). Indeed, the excessive use of social media and lack of physical activity, coupled with social isolation have long been known as a risk factor for alcoholism (Boyle et al, 2016;Peltiera et al, 2019), and this is especially the case during Covid-19 (Cerezo et al, 2021;Vogel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%